2021
DOI: 10.1097/pas.0000000000001789
|View full text |Cite
|
Sign up to set email alerts
|

Somatic-type Malignancies in Testicular Germ Cell Tumors

Abstract: The development of somatic-type malignancies (SMs) in testicular germ cell tumors (GCTs) is a rare but well-recognized phenomenon. We studied the pathologic features of 63 GCTs with SMs in the testis (n = 22) or metastases (n = 41) and correlated these features with clinical outcomes. The patients with SMs in the testis (median age, 26 y) were younger than those with metastatic SMs (median age, 38.5 y). The SMs consisted of carcinomas (n = 21), sarcomas (n = 21), primitive neuroectodermal tumors (n = 15), neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Rarely, SMs can be hematological malignancies, a combination of different forms, or undifferentiated tumors [ 7 , 13 ]. Hwang et al, in a study of 63 cases, observed that rhabdomyosarcoma was the most common histological subtype of SM for tumors found in the testis, while carcinoma, particularly adenocarcinoma, was the predominant subtype found in the metastatic sites, as in our case [ 14 ].…”
Section: Discussionsupporting
confidence: 57%
“…Rarely, SMs can be hematological malignancies, a combination of different forms, or undifferentiated tumors [ 7 , 13 ]. Hwang et al, in a study of 63 cases, observed that rhabdomyosarcoma was the most common histological subtype of SM for tumors found in the testis, while carcinoma, particularly adenocarcinoma, was the predominant subtype found in the metastatic sites, as in our case [ 14 ].…”
Section: Discussionsupporting
confidence: 57%
“…Appropriate treatment for SMT GCT is challenging 13,19 . Available studies (Table S1) concur in that, when documented solely in the primary testicular tumour, the prognosis is not adversely affected by the presence of SMT 17,20 . However, SMT present in metastatic sites shows an inferior prognosis 19,21,22 .…”
Section: Discussionmentioning
confidence: 96%
“…13,19 Available studies (Table S1) concur in that, when documented solely in the primary testicular tumour, the prognosis is not adversely affected by the presence of SMT. 17,20 However, SMT present in metastatic sites shows an inferior prognosis. 19,21,22 This too was verified in our work, with all patients showing SMT exclusively in the primary tumour, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations